2016
DOI: 10.5511/plantbiotechnology.15.1117a
|View full text |Cite
|
Sign up to set email alerts
|

An MYB transcription factor regulating specialized metabolisms in <i>Ophiorrhiza pumila</i>

Abstract: Camptothecin is a plant-derived alkaloid and important precursor of clinically used anti-tumor drugs, but little is known about regulatory mechanism of camptothecin production in plants. We show here that a MYB transcription factor, OpMYB1, isolated from Ophiorrhiza pumila is a regulator of camptothecin biosynthesis. OpMYB1 has an EAR-like motif and exhibits a transcriptional repression activity in an in vivo assay using Arabidopsis thaliana leaves. Overexpression of OpMYB1 in hairy roots of O. pumila resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Therefore, using comparative expression analysis, we identified AP2/ERFs that are specially expressed in HR when compared with CSC. From the data derived by PCR-select cDNA subtraction (Rohani et al, 2016), six out of 353 HR-specific fragments were annotated as ERF-like proteins. Full-length cDNA cloning revealed that all these six fragments constitute a part of 903-bp cDNA sequence (designated as OpERF1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, using comparative expression analysis, we identified AP2/ERFs that are specially expressed in HR when compared with CSC. From the data derived by PCR-select cDNA subtraction (Rohani et al, 2016), six out of 353 HR-specific fragments were annotated as ERF-like proteins. Full-length cDNA cloning revealed that all these six fragments constitute a part of 903-bp cDNA sequence (designated as OpERF1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Removal of adapter sequences, low-quality reads, and reads shorter than 50 bp yielded a total of over 84 million high-quality paired end clean reads (Table 2). Clean reads from individual libraries were aligned with previously described and annotated O. pumila de novo transcriptome assembly (Rohani et al, 2016) using Bowtie 2.0 (Langmead et al, 2009), and transcript abundance in FPKM was estimated using the RSEM program (Li and Dewey, 2011). More than 88% of the clean reads from each library could be aligned to a reference de novo assembly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome and metabolome analysis for engineered O. pumila cultured cell lines producing (hairy roots) or not producing (cell suspension culture) camptothecin-type alkaloids led to the identification of candidate genes involved in the biosynthesis of alkaloids and anthraquinones . Further, transcription factors, namely OpMYB1 and OpERF2, of O. pumila with functions in regulating the biosynthesis of secondary metabolites were identified using RNA-seq-based transcriptome profiling and metabolome analysis (Rohani et al, 2016;Udomsom et al, 2016). Comprehensive transcriptome and metabolome analysis, and their integration, led to the elucidation of morphine biosynthetic pathways and functional characterization of most of the genes coding for associated biosynthetic enzymes (Hagel and Facchini, 2013;Higashi and Saito, 2013).…”
Section: Integrative Omics For Understanding Complex Biological Intermentioning
confidence: 99%